Welcome to Camp Nightmare - Stine, R. L.; Copyright Paperback Collection (Library of Congress) (New York : Scholastic Inc. ; [Milwaukee, Wis. : Distributed by] Penworthy, 1993)
A creepy thriller about a nine-year-old boy whose summer stay at Camp Nightmoon becomes a living nightmare.
"An Apple paperback."
Keywords: Horror tales; Horror fiction; Fantasy fiction